Violence, Justice, and Law in Classical Antiquity - Lintott, Andrew, author.
1 online resource (716 pages)
Keywords: Violence, Justice, and Law in Classical Antiquity collects together forty-three of Andrew Lintott's most significant papers. Lintott's corpus of work exposes the fundamental reliance of ancient Romans (and Greeks) on violent measures, including their readiness to resort to violence in the manner of judicial “self-help” or political tyrannicide. The legitimation of violence in Roman culture and Roman political discourse informs the nature of Roman imperialism, and equally it is impossible to understand the illegitimate violence which characterised the political collapse of the Roman Republic without understanding its deep roots in the intellectually legitimised and legally sanctioned violence of Roman society. .